2015
DOI: 10.5194/acp-15-9577-2015
|View full text |Cite
|
Sign up to set email alerts
|

In situ, satellite measurement and model evidence on the dominant regional contribution to fine particulate matter levels in the Paris megacity

Abstract: A detailed characterization of air quality in the megacity of Paris (France) during two 1-month intensive campaigns and from additional 1-year observations revealed that about 70% of the urban background fine particulate matter (PM) is transported on average into the megacity from upwind regions. This dominant influence of regional sources was confirmed by in situ measurements during short intensive and longer-term campaigns, aerosol optical depth (AOD) measurements from ENVISAT, and modeling results from PMCA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 87 publications
(4 reference statements)
11
98
2
Order By: Relevance
“…It is noteworthy that PMCAMx/PSAT simulates that the relative contribution of sources in Paris to total PM 2.5 tends to be lower during polluted than during average days. This rather surprising result is consistent with the observation-based estimates of Beekmann et al (2014).…”
Section: Summersupporting
confidence: 79%
See 3 more Smart Citations
“…It is noteworthy that PMCAMx/PSAT simulates that the relative contribution of sources in Paris to total PM 2.5 tends to be lower during polluted than during average days. This rather surprising result is consistent with the observation-based estimates of Beekmann et al (2014).…”
Section: Summersupporting
confidence: 79%
“…This underestimation of local sources (almost 0.2 µg m −3 for summer and winter) could be explained by the behavior of fresh POA. Both the measurement-based studies of Beekmann et al (2014) and Freutel et al (2013) found that almost 62 % of the OA in the center of Paris was HOA (Primary Organic Aerosol) and cooking OA and 38 % was oxygenated OA. The discrepancy between the measurements and the model can be explained by the cooking emissions which have not been included in the PMCAMx inventory used in this study.…”
Section: Comparison Of Psat Results and Observation-based Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported that in rural environments in the Mediterranean, airborne PM and ammonium sulfate concentrations undergo a seasonal cycle characterised by a summer maximum (Bergametti et al, 1989;Kubilay and Saydam, 1995;Querol et al, 1998a, b;Rodríguez et al, 2001Rodríguez et al, , 2002. This seasonal cycle has not been reported at rural sites in central and northern Europe, where high PM events are mostly recorded in winter during stagnant episodes caused by cold temperature inversions and low wind speed (Beekmann et al, 2015;Favez et al, 2007;Monn et al, 1995;Röösli et al, 2001;Turnbull and Harrison, 2000). Long-term measurements at sites in the western and eastern Mediterranean basin by Querol et al (2009) showed that mineral matter is the major component of PM 10 (22-38 %) in both areas, with relatively high proportions in PM 2.5 (8-14 %), followed by sulfate, organic matter (OM), nitrate and ammonium.…”
Section: Introductionmentioning
confidence: 99%